Rantai Proses Pemfilletan dan Pembekuan Fillet Ikan Kakap Merah (Lutjanus malabaricus) dengan Perlakuan Karbon Monoksida di PT Inti Luhur Fuja Abadi - Fauzi, Ahmad; Ainiyah, Roisatul; Izzah, Nikmatul (Fishery Product Technology Study Program, Yudharta University, Pasuruan, 2025)
Red snapper (Lutjanus malabaricus) is a high-value fisheries commodity commonly marketed in the form of frozen fillets. To maintain product quality during processing and distribution, appropriate handling practices are required, including the application of carbon monoxide (CO) treatment. This study aimed to describe the processing chain of filleting and freezing red snapper fillet products with CO treatment at PT Inti Luhur Fuja Abadi, Beji, Pasuruan, East Java, Indonesia. A qualitative descriptive method with a case study approach was employed through direct observation, interviews, and involvement in the production process. The results showed that the processing chain consisted of raw material reception, dressing, washing, filleting, carbon monoxide treatment, freezing, packaging, and frozen storage. The application of CO treatment contributed to maintaining fillet color and appearance during frozen storage, while freezing slowed down quality deterioration. Therefore, the implementation of a controlled and standardized processing chain plays an important role in ensuring the quality and competitiveness of red snapper fillet products.